Manhaj Al-Imam Al-Shafi’i Dalam Periwayatan Hadith: Penelitian Terhadap Karya Ikhtilaf Al-Hadith : Manhaj al-Imam al-Shafi’i in the Narration of Hadith: A Study of the Works of Ikhtilaf Al-Hadith - Md Ariffin, Mohd Farhan; Mohd Rokhibi, Ibrahim Adham; Syafie, Shafiza; Harun , Muhammad Safwan (Al-Basirah Journal, 2022)
Al-Imām al-Shāfi‘ī is a famous scholar in the history of Islam and he is known as a mujtahid mutlaq. He mastered many aspects of Islamic science, including the field of hadith. His credibility in the field of hadith is often disputed by some Salafi groups, as al-Imām al-Shāfiʻī is considered only an expert in the field of fiqh. Thus, this article seeks to examine the manhaj of al-Imām al-Shāfi‘ī in the narration of hadith by examining the work of Ikhtilāf al-Ḥadīth as well as proving his prowess in the field of hadith. This study is a qualitative study that involves data collection methods through a literature review. The collected data were subsequently analyzed using inductive, deductive, content analysis and thematic methods. As a result, it was found that there were six methodologies related to hadith narration that were applied by him and were also supported by authentic arguments and evidence.